2008
DOI: 10.1039/b815899a
|View full text |Cite
|
Sign up to set email alerts
|

A multifunctional organometallic switch with carbon-rich ruthenium and diarylethene units

Abstract: The perturbation of a dithienylethene system by a ruthenium carbon-rich system, and vice versa, was used to reach a unique and sophisticated light- and electro-triggered multifunctional switch featuring multicolor electrochromism, electrocyclization at remarkably low voltage, and photo/electro tuning of electronic communication.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
64
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(70 citation statements)
references
References 20 publications
3
64
2
Order By: Relevance
“…[9] Of particular interest are the complexes [ [10] and [ClRuA C H T U N G T R E N N U N G (dppe) 2 -CC-DTE-CC-RuA C H T U N G T R E N N U N G (dppe) 2 Cl] (dppe = Ph 2 PCH 2 CH 2 PPh 2 ), [11] which display both electrochromism and electrocyclisation. Recently, Branda and Wolf [12] have shown that in the mono-platinum complex…”
Section: Pta C H T U N G T R E N N U N G (Pet 3 ) 2 a C H T U N G T Rmentioning
confidence: 99%
“…[9] Of particular interest are the complexes [ [10] and [ClRuA C H T U N G T R E N N U N G (dppe) 2 -CC-DTE-CC-RuA C H T U N G T R E N N U N G (dppe) 2 Cl] (dppe = Ph 2 PCH 2 CH 2 PPh 2 ), [11] which display both electrochromism and electrocyclisation. Recently, Branda and Wolf [12] have shown that in the mono-platinum complex…”
Section: Pta C H T U N G T R E N N U N G (Pet 3 ) 2 a C H T U N G T Rmentioning
confidence: 99%
“…The use of isolated [RuCl(dppe) 2 ] + ([2] + ) salts as an entry to acetylide complexes trans-RuCl(C"CR)(dppe) 2 and related compounds has recently begun to attract attention [12,14,27,34,35,57,58]. In this contribution, we detail a convenient preparation of acetylide complexes 3 from trans-1 that takes advantage of the ready abstraction of a chloride ligand from trans-1 by AgOTf in dichloromethane to give the key reagent [2]OTf.…”
Section: Introductionmentioning
confidence: 99%
“…Transition metals based on metal-organic complex multicolor electrochromic materials exhibit attractive properties, such as high stability and chemiluminescence. 16 However, the expense and scarcity of the precious metals, such as ruthenium, 15,16 osmium 17 and iridium, 18 limit their practical applications. Polymeric multicolor electrochromic materials with different electrochromic activation units [19][20][21] possess the advantages of easy processing, diverse resources and facile color tunability.…”
Section: Introductionmentioning
confidence: 99%
“…Because the realization of a multicolor switch is preferred in the majority of their applications in displays, [4][5][6][7][8][9][10] various electrochromic materials including polymers, 11,12 small organic molecules 13,14 and metal-organic complexes, 15 and technologies aimed at multicolor switches have been intensively explored. Transition metals based on metal-organic complex multicolor electrochromic materials exhibit attractive properties, such as high stability and chemiluminescence.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation